Feasibility of Submandibular Gland Preservation in cT1-2N0 Squamous Cell Carcinoma in the Floor of the Mouth - Du, Wei; Fang, Qigen; Liu, Shanting; Chen, Defeng; Luo, Ruihua; Zhang, Xu (Frontiers in Oncology, 2020)
Purpose: Our goal was to analyze the feasibility of submandibular gland (SMG) preservation in cT1-2N0 floor of the mouth (FOM) squamous cell carcinoma (SCC) patients. Methods: Patients with cT1-2N0 FOM SCC were retrospectively enrolled and divided into two groups according to the management of the SMG. Level 1b tissues were divided into six groups according to their location with respect to the SMG. The Kaplan-Meier method was used to calculate the locoregional control (LRC) and disease-specific survival (DSS) rates. A Cox model was used to determine the independent risk factors. Results: Twenty-nine patients underwent SMG-preserving neck dissection, and lymph node metastasis occurred in the superior group in 3 of the 37 dissections with a prevalence of 8.1% and in the anterior group in 2 of the 37 dissections with a prevalence of 5.4%. In patients without SMG preservation, lymph node metastasis occurred in the superior group in 7 of the 137 dissections with a prevalence of 5.1% and in the anterior group in 6 of the 137 dissections with a prevalence of 4.4%. The only pattern of SMG involvement was invasion by positive lymph nodes. The 5-year LRC rates for patients with SMG preservation and patients with SMG excision were 84% and 73%, respectively, and the difference was not significant (p=0.239). The 5-year DSS rates for patients with SMG preservation and patients with SMG excision were 88% and 84%, respectively, and the difference was not significant (p=0.524). Conclusions: In early-stage FOM SCC patients, SMG involvement is rare, the most common metastatic site in level 1b is the superior group, and SMG preservation does not decrease the LRC or DSS rates. Therefore, the findings suggest that there might be high feasibility of SMG-preserving neck dissection in cT1-2N0 FOM SCC.